Distinct soil microbial communities under Ageratina adenophora invasions. (20th January 2022) - Li, Q.; Wan, F.; Zhao, M.
Abstract: Ageratina adenophora is one of the most hazardous invasive weeds in China. It can form a single species community quickly and cause extensive ecological harm. The belowground microbial community can participate in nutrient transformation in soil and plays an important role in the invasiveness of exotic plant species. We selected sampling sites with different invasion levels of A. adenophora . The soil property and soil biogeochemical activity were measured in both bulk and rhizosphere soil under the aggressive weed A . adenophora and under adjacent native plants. The composition of bacterial communities was investigated using high‐throughput 16S rRNA gene sequencing. We found that the rhizosphere habitat selectively accumulated Sphingomonas and Steroidobacter and reduced the abundance of Gaiella and Gp6 regardless of plant host. The presence of A. adenophora caused a switch in microbial composition from Aeromicrobium and Marmoricola to Reyranella and Bradyrhizobium in the bulk soil, and from Gp4, Pirellula, Lysobacter and Aridibacterrae to Reyranella and Streptomyces in the rhizosphere soil. We also revealed specific microbes that closely related with N‐cycling processes. In addition, soil pH was the main factor affecting microbial communities in both bulk and rhizosphere soil. Our study confirmed that the rhizosphere environment imposed homogenous microbial communities. The invasion of A. adenophora selected specialized bacterial communities in soils and specific microbes that potentially mediated soil nutrition cycling. Our findings provide ecological explanation to explain how the underground microbes help A. adenophora invasive. Abstract : The specific bacterial groups selected by Ageratina adenophora potentially regulated soil nutrition cycling in response to plant invasion.